A modified WBANs MAC superframe using priority-criticality index table for managing pilgrims’ emergency traffic in Hajj - Shah Murtaza Rashid Al Masud; Asmidar Abu Bakar; Salman Yussof (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
During Hajj, pilgrims suffer from various emergencies that should be managed in a real-time manner thus require deploying emerging technology. Based on our research it is found that the emergency medical circumstances among the pilgrims are due to the criticality level of certain physiological conditions those are by some means rely on five major types of the physiological data rate. Five major data types include heart rate, respiratory rate, body temperature, high or low blood pressure and blood sugar respectively which are obligatory to be transmitted real-time and ahead of other non-critical traffic as delay in its transmission may jeopardise human life. Hence, by the criticality constraints of pilgrims’ physiological data, we primarily perform a traffic classification through literature review. By using classified critical traffic, we define the different priority levels to be used by WBANs hub or coordinator. Therefore, in this research, we apply an analytical method to develop the priority-criticality index table in such a way that there will be no queuing delay in the system. Since our research mainly focuses on to manage the emergency, therefore, for simplicity of critical data transmission, we modified the existing medium access control (MAC) superframe that obtains only one exclusive access period (EAP) slot. The modified MAC superframe structure is to perform efficiently even when more than one emergency traffic from different sensors aggregate to the WBANs coordinator for further transmission to the healthcare stations.